Underpinning of the sharing knowledge about immunisation (SKAI) communication approach: A qualitative study using recorded observations. Issue 6 (June 2020) - Randall, Sue; Leask, Julie; Robinson, Penelope; Danchin, Margie; Kinnersley, Paul; Witteman, Holly; Trevena, Lyndal; Berry, Nina
Highlights: Consultations have greater effectiveness when parental concerns and questions are elicited to saturation. Early agenda setting in partnership with parents helps structure of consultations. Understanding parents' motivation to change is key to guiding conversations. Recommending vaccination provides a clear message. Abstract: Objective: To refine communication strategies to assist clinician conversations with vaccine hesitant and declining parents as part of the Sharing Knowledge About Immunisation (SKAI) package. Methods: We recorded and analysed consultations held in two Specialist Immunisation Clinics in tertiary hospitals in Australia between consenting clinicians and parents. We undertook content analysis that was both iterative and informed by the Calgary Cambridge Model of health communication and motivational interviewing. Results: We found common strengths and opportunities in clinician's communication styles. Strengths included: rapport building; communicating care for both the parent and child; exhibiting depth of vaccination-specific communication skill and content knowledge. Opportunities for strengthening communication practices included: eliciting parents' concerns to saturation early in the consultation; structuring the consultation to prioritise and address parents' concerns; recognising and responding to parents' motivation to vaccinate; effectively closing consultations. Conclusion: This study has synthesised clinical communication strategies from expert vaccination communicators using well-established communication frameworks to advance a unique approach to the challenging task of addressing vaccine hesitancy and refusal. Practice implications: The clinic observations helped us to create a structured consultation guide that can enhance and provide greater structure to a clinician's existing communication skills.